USULAN PERBAIKAN KESELAMATAN KERJA UNTUK MEMINIMALKAN KECELAKAAN KERJA DENGAN PENDEKATAN JOB SAFETY ANALYSIS (JSA) PADA AREA LANTAI PRODUKSI DI PT. ALAM PERMATA RIAU - Dewi Diniaty Diniaty (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2015)
PT. Alam Permata Riau is a company that pays little attention to safety. Where in work activities are always accompanied by a potential hazard that could cause accidents at work. This study aims to determine the statistical value of workplace accidents by using Frequency Rate, Severity Rate, and Safety Score, identifying the types of occupational accidents in the production process, identifying factors that could potentially pose a hazard to workers, and propose improvements that need to be taken to minimize workplace accidents PT. Alam Permata Riau with Job Safety Analysis approach. Methodology used in this research is secondary data from the company, direct observation, and identification of occupational accidents. identification using a work accident frequency rate, severity rate, and use safety scor. The survey results revealed that the highest frequency rate was in 2014 as many as 289 accident severity rate is the highest value in 2009 sebabyak 267 days, and the safety scor show that the state of K3 PT. Riau Natural jewel in good condition with a value <= -2.00. Accidents at PT. Riau Natural jewel is caused by not wearing personal protective equipment at the time of the work, and the company should provide infrastructure K3 then conduct safety audits by the JSA against work accidents in order to reduce occupational accidents in the company.